The Information Communication Technology Implementation in English Teaching During The Covid-19 Pandemic - Yuliana Yuliana (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2021)
Online learning has become a requirement during the COVID-19 pandemic. The Ministry of Education asks the teachers and students to use online classes during the pandemic. Teaching English using ICT is a challenging condition for teachers. Not all teachers are familiar with ICT. This paper aims to describe the ICT Role and implementation in Teaching English during the COVID-19 pandemic. Method: this is a literature review. Literature was searched in Science Direct and Google Scholar databases. Keywords were COVID-19, English Teaching, ICT, implementation, role. Results revealed that ICT in English Teaching is started from CALL (Computer Assisted Language Learning), TELL (Technology-Enhanced Language Learners), LMS (Learning Management System), and blended learning. YouTube and WhatsApp are preferred to be done because it is practical. Performance-based assessment is important during teaching English subject because students can learn how to perform, speaking, and debating during the performance. In conclusion, there are many systems available for teaching English using ICT. The systems are CALL, TELL, LMS, blended, WhatsApp, YouTube, and Performance-Based Assessment. The main goal is students’ understanding of the English subjects. The choice depends on study goal, teachers’ and students’ preference also feasibilities.